Visible Light Triggered CO2 Liberation from Silver Nanocrystals Incorporated Metal–Organic Frameworks. (23rd May 2016) - Li, Haiqing; Hill, Matthew R.; Doblin, Christian; Lim, Seng; Hill, Anita J.; Falcaro, Paolo
Abstract : Widespread deployment of metal–organic frameworks (MOFs) for CO2 capture remains challenging due to the great energy‐penalty associated with their regeneration. To overcome this challenge, a new type of photodynamic carbon capture material synthesized by incorporating Ag nanocrystals with UiO‐66 (Ag/UiO‐66) framework is presented. Upon the irradiation of visible light, Ag nanocrystals within the composites serve as "nanoheaters" to convert photon energy into thermal energy locally. Driven by such light‐induced localized heat (LLH), the adsorbed CO2 within MOFs is remotely released. The CO2 desorption capacity of such Ag/UiO‐66 composites can be readily regulated by control over their Ag contents and the applied light intensity. Up to 90.5% of CO2 desorption is achieved under the investigated conditions. Distinct from the traditional light‐responsive MOFs for gas trigger release, currently developed LLH‐driven CO2 release method not only offers a promising solution to the heat‐insulating nature of MOFs, but also demonstrates a potentially low energy method to remotely regenerate MOF adsorbents given the utilization of naturally abundant visible light as efficient stimulus. Abstract : A new type of photodynamic carbon capture material with up to 90.5% of CO2 desorption capacity is synthesized via integration of silver nanocrystals with UiO‐66 metal–organic frameworks. Such a highly efficient CO2 desorption is driven by the naturally abundant visible light, confirming a promising alternative to low energy regeneration of gas adsorbents.